2018
DOI: 10.2196/humanfactors.9039
|View full text |Cite
|
Sign up to set email alerts
|

Three-Factor Structure of the eHealth Literacy Scale Among Magnetic Resonance Imaging and Computed Tomography Outpatients: A Confirmatory Factor Analysis

Abstract: BackgroundElectronic health (eHealth) literacy is needed to effectively engage with Web-based health resources. The 8-item eHealth literacy scale (eHEALS) is a commonly used self-report measure of eHealth literacy. Accumulated evidence has suggested that the eHEALS is unidimensional. However, a recent study by Sudbury-Riley and colleagues suggested that a theoretically-informed three-factor model fit better than a one-factor model. The 3 factors identified were awareness (2 items), skills (3 items), and evalua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 41 publications
3
43
3
Order By: Relevance
“…The hospital is a major and comprehensive Grade 2A hospital with approximately 2000 employees and 1200 hospital beds. Randomized clinical studies are usually based on convenient sampling [ 33 , 38 ]. In this study, trained interviewers approached patients awaiting admittance at an outpatient department at the hospital.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The hospital is a major and comprehensive Grade 2A hospital with approximately 2000 employees and 1200 hospital beds. Randomized clinical studies are usually based on convenient sampling [ 33 , 38 ]. In this study, trained interviewers approached patients awaiting admittance at an outpatient department at the hospital.…”
Section: Methodsmentioning
confidence: 99%
“…The established eHEALS model is a theoretically informed concept with an eight-item baseline for assessing a person’s ability to use eHealth resources [ 14 , 15 , 31 , 34 ]. Several studies have criticized the eHEALS model as adopting a unidimensional approach and performing insufficiently in psychometric evaluation [ 24 , 35 , 36 , 37 , 38 ]. However, others have concluded that eHEALS was a valid measurement for predicting health outcomes, and, furthermore, that it improved users’ health communication and the benefit they derive for health care services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sudbury-Riley and colleagues [ 49 ] report that eHEALS scores produce a 3-factor model of information awareness, seeking, and appraisal skills among baby boomers. Similarly, the 3-factor model of eHEALS has been confirmed among baby boomers and older adults [ 55 ], chronic disease patients [ 53 ], as well as middle age adults, with an average age of 53, in a magnetic resonance imaging and computed tomography medical imaging outpatient clinic [ 59 ]. The 3-factor structure of eHEALS scores, however, has not been reported or confirmed among younger age groups, like Millennials or members of Generation X.…”
Section: Introductionmentioning
confidence: 98%